Atom-triatom rigid rotor inelastic scattering with the MultiConfiguration Time Dependent Hartree approach - Ndengué, Steve; Meyer, Hans-Dieter (Chemical physics letters, 2017)
The inelastic scattering between a rigid rotor triatomic molecule and an atom is described within the frame of the MultiConfiguration Time dependent Hartree (MCTDH) method. Sample calculations are done on the H2O-Ar system for which a flexible 6D PES (used here in the rigid rotor approximation) has been recently computed in our group and will be presented separately. The results are compared with corresponding time independent calculations using the Arthurs and Dalgarno approach and confirm as expected the equivalence of the two methods.